Determination of the development of physical inactivity among schoolchildren - Sydykanova, M.A.; Oksikbaev, B.K.; Tergenbaeva, Zh.T.; Karasholakova, L.N.; Bekishev, K.B. (Karagandy University of the name of acad. E.A. Buketov, 2022)
This article discusses ways to determine the degree of hypodynamics among students at school and suggests a method for determining the symptoms of hypodynamics. As a result of the questionnaire, the risk groups of hypodynamia among students were identified. The physiological state of these groups can be further determined. Analyzing the results of the questionnaire, it was found out that more than a half of pupils prefer inactive form of rest in their free time. Increased appetite due to hypodynamia leads to obesity, further increasing body weight and preventing exercise. The occurrence of hypoxia due to reduced motor activity, damage to cerebral blood vessels can contribute to a decrease in memory, cause abnormalities leading to a decrease in mental performance, neurosis. The first signs of hypodynamia include weakness, sleep disturbances, headaches and overweight. Analysis of the questionnaire results showed that every tenth pupil regularly does morning exercises, a quarter attend sports clubs, moreover, an important factor limiting the motor activity of pupils is the learning process accompanied by a significant number of activities. The absence of the above signs of hypodynamia is characteristic of half of the students, and the “overweight problem” is characteristic of a quarter of the students. All this is a risk of the development of more severe consequences of hypodynamia.
Keywords: school; hypodynamia; physiological condition; hygiene; natural movement; overweight; sports; musculature; atrophy